Baby shark, Happy mommy's day - Roth, Megan; Pinkfong; Nickelodeon (Firm) (2023)
"Based on the all-new Nickelodeon series, this Level 1 I Can Read is perfect for sharing with the Baby Shark fan in your life! When Baby Shark gets ready to celebrate Mother's Day, his best friend William starts to worry about why his family looks different than everyfishy else's."--
"Nickelodeon."-- Cover.
Keywords: Baby Shark -- (Fictitious character) -- Pictorial works -- Juvenile fiction; Baby Shark -- (Fictitious character) -- Pictorial works -- Fiction; Mother's Day -- Pictorial works -- Juvenile fiction; Sharks -- Pictorial works -- Juvenile fiction; Fishes -- Pictorial works -- Juvenile fiction; Friendship -- Pictorial works -- Juvenile fiction; Marine animals -- Pictorial works -- Juvenile fiction; Mother's day -- Pictorial works -- Fiction; Sharks -- Pictorial works -- Fiction; Fishes -- Pictorial works -- Fiction; Friendship -- Pictorial works -- Fiction; Marine animals -- Pictorial works -- Fiction; Fishes; Friendship; Marine animals; Mother's Day; Sharks; Fiction; Picture books; Readers (Publications); Readers (Publications); Fiction; Picture books